(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
Soil fertility depletion is a serious problem in Ethiopian highland due to leaching of topsoil by runoff, which reduces production and productivity. This experiment conducted in Debub Ari district for two years with the aim of investigating single and combined effect of compost and FYM with inorganic fertilizer on soil fertility improvement and onion crop production. The treatment includes T1) Control, T2) Recommended NP (69/30), T3) NPSZnB (120N, 92P2O5, 20.06S, 5.89Zn, 0.66B) kg ha-1 (264 kg NPSZnB + 161 kg urea), T4) 10 t ha-1 FYM, T5) 10 t ha-1 compost, T6) 5 tha-1 FYM + 50% of treatment-3 and T7) 5 t ha-1 compost + 50% of treatment-3. Treatments are arranged in randomized complete block design with three replications. Soil before the experiment showed moderately acidic, moderate in organic matter and boron, low in sulfur high in available P and total nitrogen. The results showed significant differences among the treatments on onion plant height, bulb diameter, marketable and biological yield. The highest total yield 19.99 t ha-1, 19.59 t ha-1 and 19.25 t ha-1 was recorded from NPSZnB (120N, 92P2O5, 20.06S, 5.89Zn, 0.66B) kg ha-1, 5 t ha-1 compost + 50% of T-3 and 5 t ha-1 FYM + 50% of T-3 respectively and that increase yield by 39%, 35% and 33% over the control. Soils after the experiment become medium in sulfur remain static in available boron and total nitrogen. Economic feasibility that the maximum net benefit of 246059 and 242442 ETB ha-1 with acceptable %MRR of 290 and 1300 was obtained with the application of NPSZnB (120N, 92P2O5, 20.06S, 5.89Zn, 0.66B) kg ha-1 and 5 t ha-1 FYM + 50% of T-3, respectively. Therefore, the application of those two treatments is recommended for higher yield production in the study area. Int. J. Agril. Res. Innov. Tech. 12(2): 41-45, December 2022